Inhibition and generation of saccades: Rapid event-related fMRI of prosaccades, antisaccades, and nogo trials - Brown, Matthew R.G.; Goltz, Herbert C.; Vilis, Tutis; Ford, Kristen A.; Everling, Stefan (NeuroImage (Orlando, Fla.), 2006)
Flexible, adaptive behavior often requires the inhibition of automatic responses in favor of voluntary response generation. The antisaccade task requires active inhibition of the automatic saccade to a peripheral stimulus followed by generation of a voluntary antisaccade to the opposite location. Previous studies demonstrated greater functional magnetic resonance imaging (fMRI) activation for antisaccades than prosaccades in cortical saccade areas but did not distinguish the relative contributions of saccadic inhibition and generation. To address this question, we compared prosaccades, antisaccades, and nogo trials in a rapid event-related fMRI experiment with ten human subjects (6 female, 4 male). Trials were compound, containing a colored fixation point to cue trial type, followed by a 200-ms gap and then peripheral stimulus presentation and response. Required responses for prosaccade, antisaccade, and nogo trials, respectively, were to generate a saccade to the stimulus, look away from it, and inhibit the automatic saccade while maintaining central fixation. Frontal and supplementary eye fields, anterior cingulate cortex, intraparietal sulcus, and precuneus, exhibited surprisingly similar activation patterns for prosaccade and nogo responses, suggesting that BOLD signal in cortical saccade regions might predominantly reflect visual detection and attention processes rather than saccade generation or inhibition. These regions displayed greater activation for antisaccade responses versus prosaccade or nogo responses, possibly due to visuospatial remapping or increased attention levels in the antisaccade task. In right superior frontal sulcus, right supramarginal gyrus, and posterior cingulate sulcus, activation was greater for nogo compared to prosaccade responses, suggesting a role in active saccadic inhibition.